Risk and returns of different foreign ownership portfolios: Evidence from Vietnam stock market - Anh Phong Nguyen; Hoang Anh Nguyen; Thi Hong Minh Ho; Phu Thanh Ngo (Cogent Economics & Finance, 2019)
This study aims at assessing the risk-return profile of stock portfolios by different levels of the foreign ownership ratio. The paper also evaluates the performance of portfolios by their size and the book-to-market ratio (BTM). In this study, we apply GMM approach with the data computed from stock-related database in Ho Chi Minh Stock Exchange and Ha Noi Stock Exchange for the period 2010-2017. Our findings reveal a pronounced foreign ownership impact, whereby the increase in the foreign ownership ratio results in the upturn in stocks' liquidity, return and size but also brings about the higher risk for stocks. In addition, our empirical analyses indicate that the portfolios with the foreign ownership ratio falling either to the bottom 20% or to the top 20% outperform other portfolios
Keywords: 330; Foreign ownership; pricing model; risk and return of stock portfolio